2016
DOI: 10.1183/16000617.0052-2016
|View full text |Cite
|
Sign up to set email alerts
|

Sports-related lung injury during breath-hold diving

Abstract: The number of people practising recreational breath-hold diving is constantly growing, thereby increasing the need for knowledge of the acute and chronic effects such a sport could have on the health of participants. Breath-hold diving is potentially dangerous, mainly because of associated extreme environmental factors such as increased hydrostatic pressure, hypoxia, hypercapnia, hypothermia and strenuous exercise.In this article we focus on the effects of breath-hold diving on pulmonary function. Respiratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 62 publications
0
15
0
1
Order By: Relevance
“…The acute dangers associated with competitive apnoea are apparent and should not be underestimated, e.g. lung injury associated with glossopharyngeal insufflation (Chung et al, 2010;Mijacika & Dujic, 2016), barotrauma, syncope, drowning and shallow water blackout during depth dives (Lindholm & Lundgren, 2009); as well as cardiac arrest, especially when breath holds are performed in cold water (Hong, Song, Kim, & Suh, 1967). The longer-term health impacts of competitive static breath holding, however, remain less understood.…”
Section: Maladaptations With Apnoea Trainingmentioning
confidence: 99%
“…The acute dangers associated with competitive apnoea are apparent and should not be underestimated, e.g. lung injury associated with glossopharyngeal insufflation (Chung et al, 2010;Mijacika & Dujic, 2016), barotrauma, syncope, drowning and shallow water blackout during depth dives (Lindholm & Lundgren, 2009); as well as cardiac arrest, especially when breath holds are performed in cold water (Hong, Song, Kim, & Suh, 1967). The longer-term health impacts of competitive static breath holding, however, remain less understood.…”
Section: Maladaptations With Apnoea Trainingmentioning
confidence: 99%
“…Based on this concept, divers could not have reached more than 30–35 m depths, while in fact in 1903 a Greek sponge fisherman, Georgios Stattis, descended to 71 m holding his breath to recover the anchor of an Italian ship, the “Regina Margherita” ( Bosco et al, 2007 ). However, hemoptysis can occur during breath-hold diving, and fatal pulmonary hemorrhage has been described ( Mijacika and Dujic, 2016 ). Furthermore, rupture of the pulmonary capillaries can allow air to enter the vasculature and cause cerebral arterial gas embolism ( Kohshi et al, 2000 , 2005 ).…”
Section: Man and Watermentioning
confidence: 99%
“…But it seems that it is useful to follow this parameter. Tezlaff et al [23] showed that expiratory flows at low pulmonary volumes are one of risk factors of pulmonary barotraumas [1,[23][24][25].…”
Section: Discussionmentioning
confidence: 99%